Effect of fissure integrity on lung volume reduction using a polymer sealant* in advanced emphysema - Magnussen, Helgo; Eberhardt, Ralf; Herth, Felix (Thorax, 2012)
Rationale Interlobar fissure integrity has previously correlated with responsiveness to endobronchial lung volume reduction therapy in patients with advanced emphysema. Objective This report summarises the effect of interlobar fissure integrity on responses to treatment with a novel endoscopic tissue sealant (AeriSeal emphysematous lung sealant (ELS)) that collapses hyperinflated lung. Methods Fissure status, lung volumes, tissue density and disease heterogeneity were assessed radiographically in 28 patients (age 63.4±6.1 years, 20 men) with advanced upper lobe predominant emphysema (density=888.0±18.2 HU; upper lobe tissue density <−950=2.62±1.74). Post-treatment changes in lobar volume, pulmonary function, exercise capacity, symptoms and quality of life were compared in patients with complete fissures (CFs) and incomplete fissures (ICFs). Results ELS therapy reduced lung volumes independent of interlobar fissure integrity. In patients with upper lobe emphysema and CFs, lobar volume reduction was 214±127 ml/treatment compared with 256±175 ml/treatment in those with ICFs (p=0.453). Reductions in gas trapping and improvements in spirometry, functional capacity and quality of life were similar in patients with CFs and ICFs. Stepwise multiple regression modelling confirmed that fissure integrity did not contribute to post-treatment changes in forced expiratory volume in 1 s, residual volume/total lung capacity ratio or lobar volume measured by CT analysis. Conclusions Interlobar fissure integrity, an important determinant of responsiveness to endobronchial lung volume reduction therapy in prior studies, had minimal impact on physiological and functional responses to ELS therapy in patients with severe upper lobe predominant emphysema. Clinical trial registration number Registration numbers for trials contributing to datasets in this report: NCT00884962, NCT01051258 and NCT01181466.